Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


G(x)= x+2/x-3
0 0 0
G(x) = x+2/x-3
let g(x) =y
y=  x+2/x-3
x= y+2/y-3
x(y-3) = y+2
xy-3x-y =2
y(x-1)=  3x+2
y =    3x+2/x-1
thus        g⁻¹(x) =  3x+2/x-1

0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts